Computer Self-Efficacy, Attitude Towards Computer and Identification with Internet as Determinants of Internet Use Among Library in Public Universities in Western Nigeria - Igbeneghu, Bruno Ifaorumhe (Universitas Pendidikan Indonesia, 2023)
The study examined the extent to which computer self-efficacy, attitude towards computer and identification with Internet determined the Internet use among librarians in public universities in western Nigeria. The study adopted the descriptive research design of the ex-post facto type. The target population for the study were librarians in public universities in western Nigeria. One hundred and seventeen librarians participated in the study. Computer self-efficacy inventory, Computer attitude inventory, identification with Internet inventory, and Internet use inventory were used to obtain data. Five hypotheses were tested at 0.05 level of significance. Data were analyzed using descriptive statistics, Pearson product moment correlation and multiple regression. Results indicated that a combination of computer self-efficacy, attitude towards computer and identification with Internet had significant positive relationship with Internet use (R= 0.509, p 0.05) and contributed 25.9% of the variance in Internet use. Identification with Internet (β = 0.464, t = 4.946, P 0.05) and computer self-efficacy (β = 0.200, t = 2.370, P 0.05) were found to be significant predictors of Internet use. Internet use among librarians had significant positive relationship with identification with Internet (r = 0.455, P 0.05) and Computer self- efficacy (r = .309, P 0.05) but had no significant relationship with attitude towards computer (r = 0.098, P 0.05). Computer self-efficacy, attitude towards the computer and identification with the Internet significantly determined the use of Internet among librarians in public universities in western Nigeria. It is therefore recommended that the administrators of university libraries take these factors into account when making organizational policies.